2020
DOI: 10.26496/bjz.2015.57
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Indol-3-Acetic Acid on the biology of Galleria mellonella and its endoparasitoid Pimpla turionellae

Abstract: The effects of indol-3-acetic acid (IAA) were investigated on biological parameters of Galleria mellonella (Linnaeus, 1758) (Lepidoptera: Pyralidae) and its endoparasitoid Pimpla turionellae (Linnaeus 1758) (Hymenoptera: Ichneumonidae) reared on hosts treated with 50 to 10,000 ppm of IAA in their diet. Percent fecundity of first generation of G. mellonella females increased by 12% at 50 ppm whereas the most effective decrease, by 33%, was observed at 5,000 ppm. Percent fertility decreased by 20% at 1,000 ppm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…In a study conducted with another PGR, the effects of IAA added to the host diet were examined within the host-parasitoid interactions. Researchers found that neither the host Galleria mellonella L. (Lepidoptera: Pyralidae) nor the endoparasitoid Pimpla turionellae L. (Hymenoptera: Ichneumonidae) displayed significant changes in adult size and weight upon IAA treatment [54]. The reason for the differences between our result and others' findings may be attributed in part to the use of different insect species.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…In a study conducted with another PGR, the effects of IAA added to the host diet were examined within the host-parasitoid interactions. Researchers found that neither the host Galleria mellonella L. (Lepidoptera: Pyralidae) nor the endoparasitoid Pimpla turionellae L. (Hymenoptera: Ichneumonidae) displayed significant changes in adult size and weight upon IAA treatment [54]. The reason for the differences between our result and others' findings may be attributed in part to the use of different insect species.…”
Section: Discussioncontrasting
confidence: 92%
“…The adverse effects of PGRs on the reproductive potential of insects were attributed to their interference with the neurosecretory system [29]. There are also other investigations showing the adverse effect of PGRs on beneficial insects through the host species [34,35,[54][55][56][57][58][59][60]. For example, IAA and GA 3 added to the diet of A. grisella were shown to cause undesirable effects on some life history traits and biochemical parameters of the parasitoid A. galleriae [34,35,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stock cultures of G. mellonella and P. turionellae were maintained in the laboratory as previously described [29]. Last-instar G. mellonella larvae, each weighing 200-250 mg, were reared to the pupal stage.…”
Section: Materials and Methods (A) Insect Rearingmentioning
confidence: 99%
“…To obtain sufficient specimens for proteome and transcriptomic work, colonies of P. turionellae (Hymenoptera, Ichneumonidae) were reared in the lab according to reference [104], using pupal stages of Galleria mellonella (greater wax moth) as hosts. Adult parasitoids were collected after hatching from the host pupae and held in 1 L glass jars without a host and fed on 50% (v/v) honey solution.…”
Section: Rearing and Dissection Of P Turionellae Specimens For Protementioning
confidence: 99%